Implementation of board game based on PISA framework in exploring high school students’ scientific literacy skills of digestive system - C G Kencana; S Sriyati; D Priyandoko (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aimed to apply learning with board game based on PISA (Programme for International Students Assessment) Framework to explore the ability of high school students' scientific literacy of digestive system; using quasi-experimental research design. The quasi-experimental research design that used was the pre-test and post-test non-randomized control group. These two classes were taken and divided into experimental and control group. The sample was taken by cluster random sampling technique in experimental class (n= 31 students) and control class (n= 29 students) with the population of 11th grade students in a high school in Bandung. Students' scientific literacy skills were explored by scientific literacy tests with PISA frameworks in the form of 20 multiple choices. Based on the analysis of the Students' scientific literacy, the normalized gain in experiment class is 0.695 and control class is 0.048. Therefore, the result showed that board game based on PISA is effective because students in experiment class have higher normalized gain than control class. Teacher can use board game based on PISA framework as teaching media to improve students' scientific literacy skills.